ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN RISIKO BISNIS PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Rivan Dwi Aghnitama; Endang Tri Widyarti (Diponegoro Journal of Management, 2023)
ABSTRACT Volatility of dividend policy in the Primary Consumer Goods sector companies even though their profitability levels tend to be stable, indicates that there are several other factors that influence management in determining the company's dividend policy. This study was conducted to analyze the effect of the independent variables, namely profitability, leverage, liquidity, and firm risk against the dependent variable, namely dividend policy in the IDX Primary Consumer Goods sector companies. Ordinary Least Square (OLS) Method was used to test the hypothesis with the IBM SPSS Statistics 25 program. The results showed that the ratio of return on assets (ROA) which is a proxy of the profitability variable and the Price/Earnings Ratio (PER) which is an inverse proxy of the firm’s business risk variable, has a significant positive effect on dividend policy which is proxied by the dividend payout ratio (DPR). The leverage variable as proxied by the debt-tototal-asset ratio (DAR) has a significant negative effect on the dividend payout ratio (DPR). The liquidity variable which is proxied by the current ratio (CR) has a positive and insignificant effect on the dividend payout ratio (DPR). Thus, it can be concluded that an increase in profitability in a company will have an effect on increasing the company's dividend policy. On the other hand, the increase in leverage and the firm risk will affect the decrease in the company's dividend policy